Checking Device for Checking Compressed Air Breathing Apparatus of Fire Fighters (Texas Journal of Engineering and Technology, 2023)
The article discusses a testing device for testing breathing apparatus with compressed air used in fire and rescue units of the Ministry of Emergency Situations of the Republic of Uzbekistan. The necessity of carrying out checks of devices in the breathing simulation mode is substantiated.